Effective cost management: Applying activity - based costing in private healthcare - (haemodialysis services) - Cheow, Jen Hurn (Universiti Malaysia Sarawak, (UNIMAS), 2011)
n today's competitive environment, accurate costing information is crucial for all kinds of businesses, especially in services industry. Argued to be superior to the traditional costing management system, Activity-Based Costing system (ABC) has increasingly attracted the attention of practitioners and researchers alike as one of the strategic tools to aid managers for better decision making in various industry. The benefits of ABC system and its impacts on companies' performance have motivated numerous empirical studies on ABC system to private healthcare servic0 This case study was performed aiming at applying the Activity-based Costing method in a hemodialysis center in support its pricing strategies and also management decision making. Among the services industries, healthcare provider is one of the business that most resource consuming component. The private healthcare's are looking for a way to stay competitive in an environment where the share of indirect costs increase in the cost structure. ABC defines the costs in terms of an organization's processes or activities and determines cost associated with significant activities or event. ABC able indicates the direct and indirect cost a very detail. The ABC able to teU the management of private healthcare services the most accurate cost where related to the services or activities provided to the customers. The information provided by the ABC method has optimized the overall understanding of the cost driver process and provided the foundation for assessing performance and improvement in the hemodialysis services. ABC also can adapt to other hospital services in order to make decision in pricing and resource management. In the competitive business world, attractive pricing able to lead the market share.